The Existence of Traditional Wedding Ceremonies for the Development of Cultural Tourism in Ngilgof Tourism Village - Fiki Madilis; Sukirno, Pradina Anjarwaty (Sean Institute, 2025)
This study aims to examine the existence of traditional wedding ceremonies in the Ngilngof Tourism Village and their potential for developing cultural tourism. The research method used was qualitative with in-depth interviews and participatory observation. The results show that traditional wedding ceremonies in Ngilngof Village have rich cultural elements, including rituals, symbols, and strong local values. The local community has a positive perception of the ceremony's potential as a tourist attraction, which can provide economic benefits and increase cultural awareness. However, there are challenges in preserving traditions amidst the development of the tourism industry. This study recommends a preservation strategy that involves the local community and stakeholders to optimize the development of cultural tourism based on traditional wedding ceremonies.